Influencing Power Flow and Transient Stability by Static Synchronous Series Compensator - Md. Imran Azim; Md. Abdul Wahed; Md. Ahsanul Haque Chowdhury (IAES Indonesian Section, 2015)
In the present world, modern power system networks, being a complicated combination of generators, transmission lines, transformers, circuit breakers and other devices, are more vulnerable to various types of faults causing stability problems. Among these faults, transient fault is believed to be a major disturbance as it causes large damage to a sound system within a certain period of time. Therefore, the protection against transient faults, better known as transient stability control is one of the major considerations for the power system engineers. This paper presents the control approach in the transmission line during transient faults by means of Static Synchronous Series Compensator (SSSC) in order to stabilize Single Machine Infinite Bus (SMIB) system. In this paper, SSSC is represented by variable voltage injection associated with the transformer leakage reactance and the voltage source. The comparative results depict that the swing curve of a system increases monotonically after the occurrence of transient faults However, SSSC is effective enough to make it stable after a while.